(untitled) (Bucharest Working Papers in Linguistics, 2024)
This paper proposes a cognitive view on sentence stress patterns to discuss focus elements in both broad and narrow focus contexts. The cognitive perspective is based on the hypothesis that prosodic phrases correspond at the cortical level to cognitive binary relations between speech objects of utterances. On this view, cognitive relations are produced by a generic information packaging (IPk) mechanism that pairs constituents with different cognitive functions. At the utterance level, cognitive relations are implemented by prosodic phrases (relations) where different pitch features mark their two functional constituents. Our proposal is to assign sentence stress patterns with corresponding cognitive structural patterns of utterances. One of the two constituents of cognitive and prosodic relations is nuclear and projects its cognitive function to the whole cognitive unit which it belongs to. The paper proposes a nuclear accent analysis by connecting the cognitive functions of constituents with their phonetic/phonological features. The contours analyzed in the paper as hierarchies of cognitive/prosodic relations are selected from those used by Ladd (2008) to exemplify sentence stress patterns in broad focus statements with ascending and descending contours, and in contrastive focus statements. We conclude that, in the new perspective, different cognitive structural patterns can be assigned to contrastive/broad focus statements in different semantic contexts.